Late Neolithic tethering or trapping stones from Bargat el-Shab (Western Desert of Egypt). Function and meaning - Przemysław Bobrowski; Maciej Jórdeczka (Polish Archaeology in the Mediterranean)
Pastoral communities left numerous and varied traces of activity in the Sahara. Among them are so-called tethering/trapping stones, attested mainly in an area stretching from Algeria through Egypt to Sudan. Discovered in a variety of contexts, these originally utilitarian items with multiple functions occasionally gained importance in rituals performed by Middle Holocene pastoral communities. This paper focuses on stones found in the southern zone of the Western Desert of Egypt and discusses their function and significance in the broader context of North Africa.